The historical presence of Arab tribes and clans in the administratire regions (disputed ) ) 1800 m -1921 m) (Journal of the College of Education for Women, 2019)
(disputed areas) before the establishment of the national government in Iraq in 1921, had to search for Arab tribes and clans in which the recipe group is available as a social organization coherent based on the foundations of several of them tribalism and her Land relates know Deira in those areas during the period that preceded the establishment of the national government in Iraq in 1921, and based on the inter girls primary sources and published mostly before the establishment of the national government in Iraq, the source of their information search and direct inquiry.Research has proved that the tribes and clans of Arab exist in all districts described by (disputed), except (judicial Akre and Tilkaif) and varying degrees of time to spend and time to time, as their presence in these areas is old, was one of the natural movement of tribes and clans that were pursues meet the necessary requirements, and without political will or administrative by the Ottoman Empire, or one and Adtha.The research proved that the district centers (disputed) comprises the majority of the components of Iraq and at different rates and variable spend one center to another, and formone of the components of those Arabs urban communities and the families of the system is uncertain.Research has shown that the presence of the Yazidis in Sinjar mountain and Turkmen in the city of Tal Afar, both of which are located west of the city of Mosul, not necessarily the lack of presence of Arab tribes in both regions does not mean, Within Sinjar city does not have a non-Yazidis, but Sinjar mountain chain and Sheba included more than one Arab tribe, and the Arab presence In a small city of Tal Afar and not thus organize clans and clear, unlike the areas adjacent to the city of Tal Afar, inhabited by many Arab tribes, and the Arab tribes and clans and villages relationships and links well with peers from other ethnic groups, and did not interfere with them in violent clashes for control of the acquisition on the ground.